Implementasi Kurikulum Tingkat Satuan Pendidikan dalam Pelajaran Bahasa Di Kelas V Sekolah Dasar - Dyaristya E. P. Wismasari; Agus Wedi; Eka Pramono Adi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
This study aims to describe the planning, process implementation, and assessment of learning outcomes in language lessons in grade V elementary school. This study used a descriptive research design with observation, documentation, and interview methods. The results showed that the learning process planning had been carried out by each language teacher; the implementation of the learning process is carried out in accordance with the lesson plan, and the assessment of learning outcomes is carried out through daily tests and semester tests.